Dampak Pungutan Desa terhadap Aset dan Perekonomian Masyarakat - Setiadi, Sandi; Maulana, Rizky; Hidayat, Sarip (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the impact of village levies on village asset management and the community economy in Gunung Batu Village, Cilograng District, Lebak Regency. Using a causal quantitative approach with Structural Equation Modeling (SEM) processed using SmartPLS. This study involved 94 respondents consisting of local communities and MSME actors, selected through purposive sampling and calculated using the Slovin formula. Data were collected through questionnaires. The results of the study indicate that village levies have a positive and significant effect on village assets, as well as a positive and significant effect on the community economy. Village assets also have a positive and significant effect on the community economy. In addition, village levies have been shown to have a significant effect on the community economy when mediated by village assets. Overall findings underline the important role of village levies in increasing village assets and indirectly driving the local economy through the utilization of these assets.